An update of the Culicoides (Diptera: Ceratopogonidae) checklist for the Balkans - Pudar, Dubravka; Petrić, Dušan; Allène, Xavier; Alten, Bulent; Ayhan, Nazlı; Cvetkovikj, Aleksandar; Garros, Claire; Goletić, Teufik; Gunay, Filiz; Hlavackova, Kristyna; Ćupina, Aleksandra Ignjatović; Kavran, Mihaela; et al. (Springer Nature, 2018)
The prime significance of species belonging to the genus Culicoides Latreille, 1809 (Diptera: Ceratopogonidae) is their ability to transmit viruses such as bluetongue virus (BTV) to wild and domestic ruminants. Prior to 1998, BTV was considered exotic in Europe, but according to recent history of its outbreaks, it has become endemic in southern and eastern European countries circulating beyond its expected historical limits, into the Balkan region. The wind-borne long-distance dispersal of Culicoides spp. over water bodies and local spreading between farms emphasize the necessity of filling in the information gaps regarding vector species distribution. In most Balkan countries, data on Culicoides fauna and species distribution are lacking, or information is old and scarce.
Keywords: Culicoides, New records, Checklist, Balkans